William Shakespeare, the complete works - Shakespeare, William, 1564-1616.; Braunmuller, A. R., 1945-; Orgel, Stephen (New York : New Pelican Text, 2002)
Contains the complete text to all of Shakespeare's poems and plays; includes footnotes and an introduction to Shakespeare's life and times.
Cover title: Complete Pelican Shakespeare.
Includes bibliographical references and index.
Library Journal Starred.
Adult
Keywords: English literature